What Shall I Make? - Nandini Nayar (India Tulika Publisher)
Roll It, Pat It, Poke In Eyes, Stick On Nose And Ears - And A Ball Of Chapati Dough Can Turn Into Almost Anything! The Endearing Illustrations Follow The Quirks Of A Child's Imagination.
Grade - 3
Keywords: Read Aloud Section - N -- Read Aloud Section - N